Normobaric hypoxia impairs human cardiac energetics. - Holloway, C; Cochlin, L; Codreanu, I; Bloch, E; Fatemian, M; Szmigielski, C; Atherton, H; Heather, L; Francis, J; Neubauer, S; Robbins, P; Montgomery, H; et al. (2011)
Hypoxia causes left ventricular dysfunction in the human heart, but the biochemical mechanism is poorly understood. Here, we tested whether short-term normobaric hypoxia leads to changes in cardiac energetics and early cardiac dysfunction. Healthy male volunteers (n=12, age 24 ± 2 yr) were exposed to normobaric hypoxia in a purpose-built hypoxic chamber. The partial pressure of oxygen during end-tidal expiration (P(ET)o₂) was kept between 50 and 60 mmHg, and peripheral oxygen saturation (Sao₂) was kept above 80%. Cardiac morphology and function were assessed using magnetic resonance imaging and echocardiography, both before and after 20 h of hypoxic exposure, and high-energy phosphate metabolism [measured as the phosphocreatine (PCr)/ATP ratio] was measured using ³¹P magnetic resonance spectroscopy. During hypoxia, P(ET)o₂ and Sao₂ averaged 55 ± 1 mmHg and 83.6 ± 0.4%, respectively. Hypoxia caused a 15% reduction in cardiac PCr/ATP (from 2.0 ± 0.1 to 1.7 ± 0.1, P<0.01) and reduced diastolic function (measured as E/E', rising from 6.1 ± 0.4 to 7.5 ± 0.7, P<0.01). Normobaric hypoxia causes a rapid decrease in high-energy phosphate metabolism in the human cardiac left ventricle, which may lead to a decline in diastolic function. These findings are important in understanding the response of normal individuals to environmental hypoxia, and to situations in which disease reduces cardiac oxygen delivery.